Legal consequences of the expiration of term for imposition of the administrative penalty according to the Ukrainian legislation - Токарєва, Ксенія Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is devoted to the scientific analysis of the legal consequences of the expiration of term for imposition of the administrative penalty according to the Ukrainian legislation. The author examines problems of procedure related with consideration of court cases in this area, gives a brief theoretical overview of definitions, resolves some law enforcement problems, and analyzes court practice.